Individualised versus standard duration of antibiotic therapy in children with acute uncomplicated febrile urinary tract infection: a study protocol and statistical analysis plan for a multicentre randomised clinical trial - Ulrikka Nygaard; Naqash Sethi; Dina Cortes; Emma Louise Malchau Carlsen; Ida Maria Schmidt; Line Thousig Sehested (BMJ Open, 2023)
Introduction Febrile urinary tract infection is one of the most common bacterial infections in children. Currently, recommended antibiotic duration is 10 days. However, recent evidence suggests that 90%–95% of children with febrile urinary tract infections are afebrile and clinically improved 48–72 hours after treatment initiation. Accordingly, individualised duration of antibiotic therapy, according to the recovery time, might be more beneficial than current recommendations, but no evidence exists.Methods and analysis An open-label randomised clinical trial equally randomising children aged 3 months to 12 years from eight Danish paediatric departments with uncomplicated febrile (≥38°C) urinary tract infection to either individualised or standard duration of antibiotic therapy. Children allocated to individualised duration of antibiotic therapy will terminate antibiotic therapy 3 days after clinical improvement with no fever, flank pain or dysuria. Children allocated to standard duration will receive 10 days of antibiotic therapy. Co-primary outcomes are non-inferiority for recurrent urinary tract infection or death within 28 days after the end of treatment (non-inferiority margin 7.5 percentage points) and superiority for the number of days with antibiotic therapy within 28 days after treatment initiation. Seven other outcomes will also be assessed. A total of 408 participants are needed to detect non-inferiority (one-sided alpha 2.5%; beta 80%).Ethics and dissemination This trial has been approved by the Ethics Committee (H-21057310) and the Data Protection Agency (P-2022-68) in Denmark. Regardless of the trial’s findings (whether positive, negative or inconclusive), the results will be compiled into one or more manuscripts for publication in international peer-reviewed scientific journals and presented at conferences.Trial registration number NCT05301023.